(untitled) (Academia Science Repository, 2023)
To assist individuals desiring to benefit the worldwide work of Jehovah’s Witnesses through some form of charitable giving, a brochure entitled Charitable Planning to Benefit Kingdom Service Worldwide has been prepared. A practical analysis of the methods used in the teachingof the types of b variations allocated to students of the academic lyceum is conducted. The article was purposefully implemented.